Dialogue in action: A qualitative exploration of critical and reflective thinking through pedagogical innovation - Akyıldız, Seçil Tümen (Elsevier Sci Ltd, 2026)
The study explores students' experiences of dialogic pedagogy within an oral communication course, with particular attention to how they perceive its role in shaping their critical thinking, reflective thinking, and communicative uptake. Adopting a qualitative approach within a constructivist framework, data were collected from 15 purposefully selected undergraduate students through semi-structured interviews, classroom observations, and reflective journals. Reflexive thematic analysis illuminated how students described increased awareness of their thinking processes, greater engagement with reflection, and growing confidence in articulating ideas during dialogic activities. Grounded in Vygotsky's and Alexander's principles, dialogic pedagogy was experienced by students as creating opportunities for cognitive engagement, collaboration, and supportive speaking environments through structured peer discussions and instructor feedback. At the same time, students reported challenges related to adapting to dialogic methods, providing and applying peer feedback, and limited opportunities for English practice beyond the classroom. Taken together, the findings underscore the importance of targeted scaffolding, explicit vocabulary support, and equitable speaking opportunities in large-classroom contexts to support students' intellectual and communicative engagement within dialogically designed curricular spaces.
Keywords: Dialogic pedagogy; Critical thinking; Reflective thinking; Curricular space